Preventing Recurrent Preeclampsia by Tailored Treatment of Nonphysiologic Hemodynamic Adjustments to Pregnancy. Issue 6 (5th April 2021) - Mulder, Eva G.; Ghossein-Doha, Chahinda; Cauffman, Ella; Lopes van Balen, Veronica A.; Schiffer, Veronique M.M.M.; Alers, Robert-Jan; Oben, Jolien; Smits, Luc; van Kuijk, Sander M.J.; Spaanderman, Marc E.A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Preeclampsia is often preceded by abnormal hemodynamic changes with heterogeneous patterns in the first half of pregnancy. We assessed the effect of timely tailored correction of nonphysiological hemodynamic changes on preventing preeclampsia in a high-risk population. Primiparous women with a history of preeclampsia were invited to participate in a longitudinal program in their next pregnancy, including repeated hemodynamic assessments at 12-, 16-, 20- and 30-week gestation additional to regular pregnancy checkups. When at least 2 of the hemodynamic variables were not within physiological reference values, the hemodynamic imbalance between cardiac output and peripheral vascular resistance was counteracted with either labetalol, methyldopa, or nifedipine using a simple treatment algorithm. Normogram-guided women (n=157) were matched to 157 women receiving care as usual (power, 80%; α=0.05). Risk of recurrent preeclampsia was analyzed with logistic regression adjusted for daily low-dose aspirin or calcium supplementation. Hemodynamic changes were considered nonphysiological in 90% of women in the normogram-guided group. Twelve percent of these women developed recurrent preeclampsia compared with 22% in the care-as-usual group (adjusted odds ratio, 0.47 [95% CI, 0.25–0.88]). There were no differences between groups in gestational age at delivery (38 1 and 38 2 weeks in the normogram-guided and care-as-usual groups, respectively) and neonatal birth weight (3148 and 3180 g in the normogram-guided and care-as-usual groups, respectively). Tailored circulatory normalization of nonphysiological hemodynamic changes during pregnancy halves the risk of recurrent preeclampsia, without disadvantageous effects on offspring outcome. This simple and innovative treatment strategy may also be beneficial to other women at increased risk for preeclampsia in pregnancy. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04216706.